In‐vitro evaluation of a ciprofloxacin and azithromycin sinus stent for Pseudomonas aeruginosa biofilms. Issue 1 (6th November 2019) - Lim, Dong‐Jin; Skinner, Daniel; Mclemore, John; Rivers, Nick; Elder, Jeffrey Brent; Allen, Mark; Koch, Connor; West, John; Zhang, Shaoyan; Thompson, Harrison M.; McCormick, Justin P.; Grayson, Jessica W.; et al.
Abstract : Background: Chronic rhinosinusitis (CRS) is a chronic inflammatory disease characterized by persistent inflammation and bacterial infection. Ciprofloxacin and azithromycin are commonly prescribed antibiotics for CRS, but the ability to provide targeted release in the sinuses could mitigate side effects and improve drug concentrations at the infected site. This study was aimed to evaluate the efficacy of the novel ciprofloxacin‐azithromycin sinus stent (CASS) in vitro. Methods: The CASS was created by coating ciprofloxacin (hydrophilic, inner layer) and azithromycin (hydrophobic, outer layer) onto a biodegradable poly‐l ‐lactic acid (PLLA) stent. In‐vitro evaluation included: (1) assessment of drug‐coating stability within the stent using scanning electron microscopy (SEM); (2) determination of ciprofloxacin and azithromycin release kinetics; and (3) assessment of anti‐biofilm activities against Pseudomonas aeruginosa . Results: The ciprofloxacin nanoparticle suspension in the inner layer was confirmed by zeta potential. Both ciprofloxacin (60 µg) and azithromycin (3 mg) were uniformly coated on the surface of the PLLA stents. The CASS showed ciprofloxacin/azithromycin sustained release patterns, with 80.55 ± 11.61% of ciprofloxacin and 93.85 ± 6.9% of azithromycin released by 28 days. The CASS also significantly reduced P aeruginosa biofilm mass compared with bare stents and controls (relative optical density units at 590‐nm optical density: CASS, 0.037 ± 0.006; bare stent, 0.911 ± 0.015; control, 1.000 ± 0.000; p < 0.001; n = 3). Conclusion: The CASS maintains a uniform coating and sustained delivery of ciprofloxacin and azithromycin, providing anti‐biofilm activities against P aeruginosa . Further studies evaluating the efficacy of CASS in a preclinical model are planned.